REGULAR AND IRREGULAR BAROCLINIC WAVES IN A MARTIAN GENERAL-CIRCULATION MODEL - A ROLE FOR DIURNAL FORCING - Collins, M; Lewis, S; Read, P (1995)
The development and evolution of baroclinic transient waves are simulated in a high resolution, general circulation model (GCM) of the Martian atmosphere, including simulations both with and without a representation of the diurnal cycle of solar heating. Simulations with diurnally-averaged insolation are found to develop highly regular baroclinic transients during northern hemisphere autumn, winter and spring seasons, characterized by zonal wavenumber 1 or 2 and periods of 2-6 sols (a sol being a Martian day). With a diurnal cycle, however, transients are found to be significantly more irregular throughout the winter season, sporadically changing their dominant wavenumber and frequency, and resemble more closely data from the Viking Lander time series. These results are discussed with reference to some simple conceptual models in nonlinear dynamics, in terms either of a periodically-perturbed, self-exciting oscillator, or of attractor-merging near a crisis in a periodically perturbed bistable system.